Analisa Kelas Kemampuan Kelompok Tani Di Kabupaten Sijunjung Sumatera Barat - Ade Putra; Fuad Madarisa; Zulvera (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This study aims to assess and analyze the class ability of farmer groups in Sijunjung District, West Sumatra. The research was conducted for three months, from September to November 2022 in farmer groups from 4 sub-districts: Sijunjung sub-districts, IV Nagari sub-districts, Koto VII sub-districts, and Tanjung Gadang sub-districts. The population of this research was all farmer groups in Sijunjung District. Furthermore, samples were randomly selected using the Slovin formula, and 92 samples were assessed using a questionnaire/assessment guide. Then the score of each group was calculated and grouped into four classes of farmer group abilities. The determination of respondents was proportional to the class level of the farmer group, namely beginner, advanced, intermediate, and main classes. Analysis of farmer group ability class referad to the guideline of farmer group class ability (Regulatory chief BPPSDMP : 168/Per/SM.170/J/11/11), namely assessment in planning, organizing, carrying out activities, controlling and reporting, and developing farmer group leadership. The results of calculating scores are grouped into several ability classes, which are then used for developing strategies like coaching, escorting, and mentoring. There ware: 28 farmer groups (30.4%) which were beginner class, 57 groups (62%) of advanced class, and seven groups of farmers (7.6%) were middle class. Mean while, there were no farmer groups in the main class. Regarding planning activities obtained a total score of 38.57; organizing activities of 54.28; the ability to carry out activities 37.52; activity reporting of 5.22; and developing the leadership of 11.51. Among the five aspects, the reporting aspect was the lowest score